2009
DOI: 10.1111/j.1365-2141.2009.07742.x
|View full text |Cite
|
Sign up to set email alerts
|

NF‐E2 overexpression delays erythroid maturation and increases erythrocyte production

Abstract: The transcription factor Nuclear Factor-Erythroid 2 (NF-E2) is overexpressed in the vast majority of patients with polycythaemia vera (PV). In murine models, NF-E2 overexpression increases proliferation and promotes cellular viability in the absence of erythropoietin (EPO). EPO-independent growth is a hallmark of PV. We therefore hypothesized that NF-E2 overexpression contributes to erythrocytosis, the pathognomonic feature of PV. Consequently, we investigated the effect of NF-E2 overexpression in healthy CD34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
2
16
1
Order By: Relevance
“…Delayed erythroid maturation has previously been observed by elevating NF-E2 levels in human CD34 + hematopoietic stem cells. 32 Our current data thus corroborates the importance of correct NF-E2 levels for physiological erythroid maturation. Delayed maturation can result from inefficient or absent elimination of internal organelles from maturing reticulocytes.…”
Section: Discussionsupporting
confidence: 79%
“…Delayed erythroid maturation has previously been observed by elevating NF-E2 levels in human CD34 + hematopoietic stem cells. 32 Our current data thus corroborates the importance of correct NF-E2 levels for physiological erythroid maturation. Delayed maturation can result from inefficient or absent elimination of internal organelles from maturing reticulocytes.…”
Section: Discussionsupporting
confidence: 79%
“…3 Indeed, recently LeGO vectors have successfully been used in both murine and human HSC for short hairpin RNAmediated transcriptional silencing. 4,16 In this study, we have shown that LeGO vectors facilitate efficient gene expression in (human) MSCs, which represent a highly relevant target. 12,17 In addition, the novel LeGO vectors containing the CAG promoter 14 have widened the field of potential applications.…”
Section: Discussionmentioning
confidence: 87%
“…We have recently shown that NF-E2 overexpression delays the early phase of erythroid maturation, resulting in an expansion of erythroid progenitors, thereby increasing the number of erythrocytes derived from one CD34 ϩ cell. 10 These data propose a role for NF-E2 in mediating the dysregulated erythrocytosis of PV.…”
Section: Introductionmentioning
confidence: 88%